AN ANALYSIS OF FLOUTING OF MAXIMS DONE BY MAIN CHARACTERS IN LA LA LAND MOVIE - Wahyuni, Mery; Arifin, M. Bahri; Lubis, Indah Sari (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
Maxims are the rules of cooperative principle which is proposed by Grice in 1975. These maxims are used in conversation in order to make communication run smoothly. However, people often do not observe the maxim to deliver meaning implicitly; it is called as flouting of maxim. Flouting of maxim does not only happen in daily conversation but also occurs in literary work such as movie entitled La La Land. Therefore, this research was focused on analyzing the flouting of maxims which was done by main characters in La La Land movie. This research aimed at revealing kinds of maxim flouted by the main characters and also identifying the implied meaning behind their utterances. This research was conducted by using content analysis qualitative method since it focused on understanding language phenomena deeply. Data were taken from movie in the form of utterances. Dealing with the purposes of the research above, it was found that main characters flouted all kinds of Gricean maxim. There were 44 data that contained flouting of maxims in the movie. In addition, it was also found the implied meaning behind main characters’ utterances depending on the context of conversation. Most of the implied meaning contained of insulting, rebuking, requesting, and praising.Maksim merupakan aturan dalam prinsip kerja sama yang diusulkan oleh Grice pada tahun 1975. Maksim digunakan dalam percakapan untuk membuat komunikasi berjalan lancar. Namun, orang sering tidak mematuhi maksim untuk menyampaikan makna secara implisit; hal ini disebut sebagai pelanggaran maksim. Pelanggaran maksim tidak hanya terjadi dalam percakapan sehari-hari tetapi juga terjadi dalam karya sastra, seperti film berjudul La La Land. Oleh karena itu, penelitian ini difokuskan pada analisis pelanggaran maksim yang dilakukan oleh karakter utama dalam film La La Land. Penelitian ini bertujuan untuk menemukan jenis maksim yang dilanggar oleh para karakter utama dan juga mengidentifikasi makna tersirat di balik ucapan mereka. Penelitian ini dilakukan dengan menggunakan metode kualitatif analisis isi karena berfokus pada pemahaman mengenai fenomena bahasa secara mendalam. Data pada penelitian ini diambil dari film dalam bentuk ucapan. Berkaitan dengan tujuan penelitian di atas, ditemukan bahwa para karakter utama mencemooh semua jenis maksim Gricean. Ada 44 data yang berisi pelanggaran maksim dalam film. Selain itu, ditemukan juga makna tersirat di balik ucapan karakter utama tergantung pada konteks percakapan. Sebagian besar makna tersirat mengandung ujaran yang berfungsi untuk menghina, memarahi, meminta, dan memuji.